Management accounting is a component of the general accounting information system - Pushkar, Mykhailo; Pushkar, Mykhailo (Herald of Economics, 2024)
Introduction. Despite a significant number of scientific publications that relate to the problems of the methodology and organization of management accounting, in practice it does not spread not so much because of the resistance of accounting specialists, although they are also not too inclined to its implementation, but because managers ignore accounting information in their work . However, managers of the operational level without accounting information cannot carry out full control of the activities of executors, which acts as the final block of the management cycle. Purpose of the study is to prove that management accounting, as an innovative type of obtaining structured information, has a special value for managers of the operational level, since they are at the base of the pyramid, where the added value of the enterprise is born and the financial result is formed. Methods of researching management accounting problems include not only narrowly special ones - analysis, synthesis, logic, classification, analogy, genesis, modeling, but also scientific (fundamental) ones - historical, dialectical, systemic, monographic, sociological. Results of the study indicate the need to revise the content of the theory of accounting science. The authors of the article insist on the need to create a perfect model of management accounting as a subsystem of the general information system of accounting, the authors emphasize the methodological issues of developing its model, which can be adapted in various sectors of the economy. Prospects. Management accounting needs protection from a simplified view of information resources for management from the perspective of traditional financial accounting on the problem of data collection and processing. It is necessary to direct the efforts of scientists to the development of such a general theory of accounting, in which there would be a place for the financial, managerial and strategic subsystems of the accounting system based on an interdisciplinary matrix, after which we can talk about an intellectually mature accounting system and recommend its practical implementation at enterprises.